Retention in care for type 2 diabetes management in Sub‐Saharan Africa: A systematic review. Issue 4 (15th February 2023) - Garrib, Anupam; Njim, Tsi; Adeyemi, Olukemi; Moyo, Faith; Halloran, Natalie; Luo, Huanyuan; Wang, Duolao; Okebe, Joseph; Bates, Katie; Santos, Victor Santana; Ramaiya, Kaushik; Jaffar, Shabbar
Abstract: Objective: Diabetes prevalence has risen rapidly in Sub‐Saharan Africa, but rates of retention in diabetes care are poorly understood. We conducted a systematic review and meta‐analysis to determine rates of retention in care of persons with type 2 diabetes. Methods: We searched MEDLINE, Global Health and CINAHL online databases for cohort studies and randomised control trials (RCTs) published up to 12 October 2021, that reported retention in or attrition from care for patients with type 2 diabetes in Sub‐Saharan Africa. Retention was defined as persons diagnosed with diabetes who were alive and in care or with a known outcome, while attrition was defined as loss from care. Results: From 6559 articles identified, after title and abstract screening, 209 articles underwent full text review. Forty six papers met the inclusion criteria, comprising 22, 610 participants. Twenty one articles were of RCTs of which 8 trials had 1 year or more of follow‐up and 25 articles were of non‐randomised studies of which 19 had 12 months or more of follow‐up. A total of 11 studies (5 RCTs and 6 non‐randomised) were assessed to be of good quality. Sixteen RCTs were done in secondary or tertiary care settings. Their pooled retention rate (95% CI) was 80% (77%, 84%) in the control arm. Four RCTs had been done in primary care settings and their pooled retention rate (95% CI) was 53% (45%, 62%) in the control arm. The setting of one trial was unclear. For non‐randomised studies, retention rates (95% CI) were 68% (62%, 75%) among 19 studies done in secondary and tertiary care settings, and 40% (33%, 49%) among the 6 studies done in primary care settings. Conclusion: Rates of retention in care of people living with diabetes are poor in primary care research settings.